Cold and hot water recovery in elite youth football players: Thermal adaptations during a ten-week training period - Folkesson, M.; Pernigoni, M.; Frolova, A.; Montiel-Rojas, D.; Brazaitis, M.; Edholm, P. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Considerable physical demands are associated with frequent training sessions and matches in elite football and require optimal strategies for recovery. For this purpose, many elite players use immersion in cold (CWI) and/or hot water (HWI) following training and matches. Although shown to enhance recovery parameters, these approaches are physically stressful for the players, involving sweating or shivering, as well as discomfort. At present, little is known about the effects of long-term exposure to post-exercise CWI and HWI. The aim of the current study was to assess thermal adaptations to post-exercise CWI and HWI in elite youth football players during an intervention-period of ten weeks.